PEMBERDAYAAN SISWA MELALUI PENERAPAN KURIKULUM 2013 DI SEKOLAH - halijah, sarifa (An - Nisa`, 2015)
Learning curriculum in 2013 is learning competencies to strengthen the learning and authentic assessment process to achieve competence attitudes, knowledge and skills. Strengthening the learning process is done through a scientific approach, namely learning that encourages students are better able to observe, ask, try / collect data, associate / reasoning, and communicate. The purpose of the curriculum in 2013 is for a human menpersiapkan Indonesia in order to have the ability to live as individuals and citizens who believe, productive, keratif, innovative, effective and capable of contributing to society, nation, state, and world civilization. Curriculum 2013 can facilitate students to learn more actively creative and innovative so that by itself can be empowering students than before the implementation of the curriculum 2013. This is possible because it is through the implementation of this curriculum students are actively proceeding seeking, experience and find their